Analysis and Design of a Knowledge Management System Using the Fernandez Method in the IT Operation Center Unit (Case Study: PT Citilink Indonesia) - Gilang Banuaji; Husni Sastra Mihardja; Gerry Firmansyah; Habibullah Akbar (Asian Journal of Social and Humanities, 2023)
The effect of improving business quality on companies is influenced by developments in technology and information. Utilization of Knowledge Management System (KMS) is one of the efforts to improve the quality of the company's business. In a company, the role of knowledge management is very important so that the company can grow rapidly. For the application of good organizational knowledge requires a planned and systematic knowledge management. The benefits derived from implementing knowledge management in companies are that it can improve service to customers, increase efficiency in processes and work methods, increase the number of services or products and save costs and time. The study of this matter, the IT Operation Center (ITOC) unit has difficulties in terms of sharing knowledge in the company, therefore a study is needed entitled "Analysis of Knowledge Management System Design Using the Fernandez Method in the IT Operation Center Unit (Case Study: PT Citilink Indonesia)” then the application of this Knowledge Management System can provide convenience for employees who have some problems related to IT operations.